Implementation of adaptive asn core values through the development of digital teaching materials based on google sites and youtube in publication media materials - Arsyil Waritsman; Hirza Rahmayati (Balai Diklat Keagamaan Ambon, 2024)
This research aims to produce digital teaching materials based on Google Sites and YouTube in published media materials for scientific writing training that fulfil aspects of validity, practicality, and effectiveness as part of efforts to realize the core values ​​of Adaptive ASN The research method used is the Research and Development (R&D) method using the ADDIE model. The instruments used in this research include an assessment sheet for the validity of teaching materials, an assessment sheet for the practicality of teaching materials, and evaluation questions to measure the effectiveness of teaching materials. Digital teaching materials are valid if the assessment results from experts are at least in the excellent category. Digital teaching materials are said to be practical if the assessment results from respondents are at least in the excellent category. Teaching materials are effective if the average test score is more than 75. After going through research and development, a product was obtained through digital teaching materials based on Google Sites and YouTube on published media materials for scientific writing training that met the aspects of validity, practicality, and effectiveness. The results of this research show the contribution of trainers as part of ASN in implementing the core values ​​of Adaptive ASN. Apart from that, the results of this research can be an example of developing digital teaching materials that are suitable for training and will have an impact on improving the quality of training management.